Crustasea and makrophyta plant association in the swamp area of the Sawah Village, Kampar District, Riau Province. - Pascalia Dita; Efawani Efawani; Windarti Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThere are many types of makrophyta and crustasea in the swamp area in the Sawah Village, but there is no information on the association of those organisms. A research aims to understand the type of makrophyta, type of crustasea and association of makrophyta and crustasea, a research has been conducted in August–September 2018. Sampling were conducted once/week for a month period.Macrobrachium oxyphilus and Parathelphusa parduswere found around the community of Barclaya sp., Hydrilla verticilata and Pistia stratiotes.M. oxyphilus and P. parduswere not found around the community of Paspalum sp.. Even though the plants are different but the type of crustasea present is similar. Based on data obtained, it can be concluded that there was specific association between makrophyta and crustasea species in the swamp area in the Sawah Village. Keywords: Makrophyta, Crustasea assosiation, Aquatic plant, Sawahvillage swamp